Ten Jatakas: The Evolution of Contemporary Created Illustrations - Kacharoen, Nikorn (Dhammathas Academic Journal, 2024)
This academic article aims to synthesize knowledge from the evolutionary process of creating contemporary illustrations related to the "Ten Jatakas" folklore series, which promotes ethics, morality, visual art, and lines in the dissemination to the public. It results from the synthesis of knowledge from various sources, spanning from the past to the present. This contributes to the extraction of valuable content for each Jataka story, leading to the creation of illustrations in the "Ten Jatakas" series. These illustrations are tailored to be age-appropriate for children and convey the moral teachings inherent in each Jataka story, which is linked to everyday life experiences, making learning and understanding easier for children.